Determinants of the adoption of modern agricultural technologies from the point of view of Farmers in the center of Al-Shirqat District /Salah Al-Din Governorate - Khairallah Faraj Sabhan Al-Jubouri (Turkish Journal of Agriculture: Food Science and Technology)
This research paper identifies the Determinants influencing the adoption of modern agricultural technologies from the perspective of farmers in the Shirqat District, Salah Al Din Governorate. The adoption Determinants were categorized into three main domains: chemical technology constraints, biological technology constraints, and physical technology constraints. The study also examined variations in farmers' perspectives based on selected personal characteristics, including age, type of land ownership, possession of production tools and equipment, exposure to information sources, and attitude toward using modern technologies. Furthermore, the dominos were ranked in descending order based on the severity of adoption constraints. The study population included all 236 farmers in The Shirqat District who had adopted Delete modern agricultural technologies. A stratified sample of 47farmers, representing 20% of the population, was selected. A structured questionnaire was developed, consisting of two parts: the first part addressed farmers personal variables, while the second part contained 40 items related to adoption constraints, distributed across scale (high, moderate, low) was used for assessment, The scale size for the respondents ranged from (40-120) degrees. Data were collected through personal interviews, coded, and analyzed using SPSS software, employing statistical tools such as frequency distribution, range, percentage, arithmetic mean and variance. Data was collected from 10-11-2024 to 25-12-2024. Results showed that 87.24% of respondents fell within the moderate to high levels of adoption constraints, indicating a generally increasing trend. The domains were ranked by constraint severity as follows: chemical technology, biological technology, and physical technology. Significant differences were found in farmers' views based on most studied variable (age, land ownership, information exposure and attitudes). However, no significant differences were observed regarding possession of production equipment. The findings underscore the importance of considering these variable when designing agricultural extension and training programs. The study recommends enhancing access to information sources and promoting the use of proven, high-quality technologies to reduce adoption barriers and lower the financial burden on farmers.